Electrochemical generation of palladium volatile species enhanced with Sn(ii): application for detection of Pd(ii) by pyrolytic graphite-coated furnace atomic absorption spectrometry. Issue 5 (7th March 2019) - Shams, Alireza; Ashraf, Narges; Arbab-Zavar, Mohammad Hossein; Masrournia, Mahboubeh
Abstract : Electrochemical generation of palladium volatile species is performed using the tungsten-inert gas welding electrode enhanced with Sn(ii ). Abstract : Herein, a novel sample derivatization and introduction system, based on electrochemical generation of palladium volatile species (PdVS), has been developed for determination of Pd concentration via pyrolytic graphite-coated furnace atomic absorption spectrometry. PdVS were produced in the cathode chamber of a home-made electrochemical vapor generation cell in which a tungsten-inert gas (TIG) welding electrode and Sn(ii ) served as the cathode and the enhancement reagent, respectively. The produced PdVS were transferred into a pyrolytic graphite-coated furnace by a stream of argon carrier gas where they were trapped and atomized. Plackett–Burman experimental design was used to screen the influential experimental parameters. The effect of significant influential parameters on the method sensitivity was evaluated and optimized. Under optimum operating conditions, the calibration curve for Pd was constructed and shown to be linear in the Pd concentration range of 7.5 to 110 ng L −1 . Detection (3 s b / m ) and quantification (10 s b / m ) limits of the proposed method were evaluated using 10 blank samples and found to be 2.1 ng L −1 and 7.1 ng L −1, respectively. The relative standard deviation ( n = 7, at 50 ng L −1 concentration level) was 5%. The accuracy of the proposed method was checked by analysing two different certified reference materials which yielded the recoveries of 105% and 81% for Pd.